Dysfunction and Deviation in the Role of Foundation Organs in Indonesia - Mukri, Syarifah Gustiawati; Aji, Ahmad Mukri; Yunus, Nur Rohim (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Foundations, as non-profit legal entities, play a crucial role in supporting social, educational, religious, and humanitarian activities in Indonesia. However, in practice, many foundations still fail to carry out their organisational functions in accordance with applicable legal provisions. This study aims to analyse in depth the roles and tasks of trustees, Management, and Supervisors of foundations, as regulated in Law No. 28 of 2004, an amendment to Law No. 16 of 2001. It seeks to identify the causes of deviations and structural dysfunction in the management of foundations. This study employs a qualitative, juridical-normative, and empirical approach, utilising data collection techniques that include literature reviews and interviews with representatives from several foundations in Indonesia. The study's results indicate that a gap remains between legal norms and their implementation in the field, particularly in areas such as abuse of authority, conflicts of interest, and inadequate internal supervision systems within foundations. This is due to a lack of understanding of the role of each organ and suboptimal supervision by the Trustees and Supervisors. Therefore, efforts are needed to strengthen institutional and regulatory capacity, as well as legal education for foundation actors, to improve the governance and accountability of foundations sustainably.Keywords: Foundation; Trustees; Management; Supervisor; Law No. 28 of 2004; Non-Profit; Governance